Kemiskinan Dalam Al-Qur’an - Abdul Mu'is (Jurnal Istiqro, 2021)
the Qur'an as a Muslim holy book not only offers an improvement of relationship between man and his god, but the Qur'an also offers improvement of ethical (moral) towards human values ​​that uphold their rights and obligations. The Qur'an, which is believed to have absolute truth and does not change, is confronted with the ever-changing phenomenon of life. The change in this phenomenon has led commentators to look for various solutions offered by the Koran. One problem with society is poverty. Poverty is a common problem in the effort to build human culture and civilization that upholds human values. Discuss poverty with the perspective Qur'an, with the purpose of tracking, mapping and finding solutions based on bids Koran. The solution offered by the Qur’an is to divide obligations to resolve poverty into individual obligations, the obligations of others, and the obligations of the state.